Tropical Agroforestry - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
P Huxley, Blackwell Science. 1999.ISBN 0 632 04047 5.£69.50 Euro 108.60(See earlier Blackwell Science reference for address)